Mapping Tomorrow’s Teaching and Learning Spaces: A Systematic Review on GenAI in Higher Education - Tillmanns, Tanja; Salomao Filho, Alfredo; Rudra, Susmita; Weber, Peter; Dawitz, Julia; Wiersma, Emma; Dudenaite, Dovile; Reynolds, Sally (Trends in Higher Education, 2025)
This collective systematic literature review is part of an Erasmus+ project, “TaLAI: Teaching and Learning with AI in Higher Education”. The review investigates the current state of Generative Artificial Intelligence (GenAI) in higher education, aiming to inform curriculum design and further developments within digital education. Employing a descriptive, textual narrative synthesis approach, the study analysed literature across four thematic areas: learning objectives, teaching and learning activities, curriculum development, and institutional support for ethical and responsible GenAI use. The review analysed 93 peer-reviewed articles from eight databases using a keyword-based search strategy, a collaborative coding process involving multiple researchers, in vivo coding and transparent documentation. The findings provide an overview of recommendations for integrating GenAI into teaching and learning, contributing to the development of effective and ethical AI-enhanced learning environments in higher education. The literature reveals consensus on the importance of incorporating GenAI into higher education. Common themes like mentorship, personalised learning, creativity, emotional intelligence, and higher-order thinking highlight the persistent need to align human-centred educational practices with the capabilities of GenAI technologie
Keywords: generative artificial intelligence; higher education; academic integrity; guidelines; AI literacy